Novel Electron Transport Layer Material for Perovskite Solar Cells with Over 22% Efficiency and Long‐Term Stability. (6th September 2020) - Li, Fumin; Shen, Zhitao; Weng, Yujuan; Lou, Qiang; Chen, Chong; Shen, Liang; Guo, Wenbin; Li, Guangyong
Abstract: The electron transport layer (ETL) has an important influence on the power conversion efficiency (PCE) and stability of n‐i‐p planar perovskite solar cells (PSCs). This paper presents an N‐type semiconductor material, (CH3 )2 Sn(COOH)2 (abbreviated as CSCO) that is synthesized and prepared for the first time as an ETL for n‐i‐p planar PSCs, which leads to a high PCE of 22.21% after KCl treatment, one of the highest PCEs of n‐i‐p planar PSCs to date. Further analysis reveals that the high PCE is attributed to the excellent conductivity of CSCO because of its more delocalized electron cloud distribution due to its unique −O=C−O− group, and to the defect passivation of the Cs0.05 (FA0.85 MA0.15 )0.95 Pb(I0.85 Br0.15 )3 (denoted as CsFAMA) perovskite through the interaction between the O (Sn) atoms of CSCO and the Pb (halogen) atoms of CsFAMA at CSCO/CsFAMA interface, while the traditional ETL materials such as SnO2 film lack this function. In addition to the high PCE, the optimal PSCs using CSCO as ETL show remarkable stability, retaining over 83% of its initial PCE without encapsulation after 130 days of storage in ambient conditions (≈25 °C at ≈40% humidity), much better than the traditional SnO2 ‐based n‐i‐p PSCs. Abstract : An N‐type semiconductor material, (CH3 )2 Sn(COOH)2 (CSCO), is prepared for the first time as an electron transport layer for n‐i‐p planar perovskite solar cells, which leads to one of the highest power conversion efficiencies of 22.21%, and to remarkable stability, retaining over 83% of its initial power conversion efficiency without encapsulation after 130 days of storage in ambient conditions.